"Aggregation induced phosphorescence" active "rollover" iridium(iii) complex as a multi-stimuli-responsive luminescence material1. Issue 14 (14th April 2015) - Alam, Parvej; Kaur, Gurpreet; Chakraborty, Shamik; Roy Choudhury, Angshuman; Laskar, Inamur Rahaman
<x xml:space="preserve">Abstract</x> An 'aggregation induced phosphorescence (AIP)' active rollover complex was synthesized and tested it's potentiality as multi-stimuli-responsive smart luminescence material.